Routine Multidisciplinary Review of Severe Maternal Morbidity Is Associated with a Reduction in Preventable Cases of Severe Maternal Morbidity - Ozimek, John A.; Greene, Naomi; Geller, Andrew; Zakowski, Mark; Wong, Melissa S.; Franco, Rachel; Kilpatrick, Sarah J. (American Journal of Perinatology, 2020)
Objective Severe maternal morbidity (SMM) has increased by 45% in the United States and is estimated to affect up to 1.5% of all deliveries. Research has not yet been conducted that demonstrates a benefit to multidisciplinary review of SMM. The aim of our study was to determine if standardized, routine review of the cases of SMM by a multidisciplinary committee results in a reduction of potentially preventable cases of SMM.Study Design A retrospective cohort study of all women admitted for delivery at Cedars-Sinai Medical Center from March 1, 2012 to September 30, 2016. Our cohort was separated into two groups: a preintervention group composed of women admitted for delivery prior to the implementation of the obstetric Quality and Peer Review Committee (OBQPRC), and a postintervention group where the committee had been well established. Cases of confirmed SMM were presented to a multidisciplinary research committee, and the committee determined whether opportunities for improvement in care existed. The groups were compared with determine if there was a decreased incidence of preventable SMM following the implementation of the OBQPRC standardized review process.Results There were 30,319 deliveries during the study period; 13,120 deliveries in the preintervention group; and 13,350 deliveries in the postintervention group (2,649 deliveries during the transition period). There was no difference in the rate of SMM between the preintervention (125; 0.95%) and postintervention (129; 0.97%) groups, (p = 0.91). There was a significantly lower rate of opportunity for the improvement in care in the postintervention group (29.5%) compared with the preintervention group (46%; p = 0.005).Conclusion We demonstrated a significant reduction in the rate of potentially preventable SMM following the implementation of routine review of all SMM suggesting that this process plays an important role in improving maternal care and outcomes.Key Points
Keywords: maternal mortality; multidisciplinary review; prevention; severe maternal morbidity